Aspectos físicos e fisiológicos de sementes de quebra-pedra (Phyllanthus niruri L.) - Granja, João Antônio de Almeida (2017)
The species Phyllanthus niruri L., popularly known as Stone-Breaker, is a medicinal plant widely used by mankind throughout its history. It is mainly used to aid in the elimination of kidney stones and there are already studies that prove its potential hepatoprotective, anti-inflammatory and antioxidant. There are several researches regarding the medical and pharmacological aspects of this species, however, there is little research on its agronomic aspects, especially with regard to the characteristics of the seeds. The objective of this work was to analyze the physical aspects, the germinative behavior and the infrared spectrum near the rock breaking seeds, relating them to their coloring. It was observed that the seeds showed heteromorphism and were therefore divided according to their coloration in brown and yellow, and the following parameters were evaluated: weight of one thousand seeds, X-ray analysis, seed biometry, germination, speed index Germination (IVG) and near-infrared spectra. The tetrazolium test was also performed to identify viable seeds among the remaining seeds at the end of the germination test. Four temperatures (25, 30, 35 oC and alternating 25 - 35 oC) and two light regimes (light and dark) were used to evaluate germination. Germination was observed only in brown seeds and the highest values of this parameter were observed in the presence of light with a temperature of 25 oC. It was also observed that the brown seeds are more developed than the yellow seeds and it is recommended the use of the brown seeds for an eventual cultivation. In the second chapter of the study, only the brown seeds were used, and the objective was to verify dormancy as well as to overcome it. Three experiments were carried out, using several treatments of dormancy overcoming. In the first one, four treatments were established: control, hot water, 50 mM KNO3 and 10 [micro]M GA3 and two light regimes (light and dark). Two other experiments were carried out from the results of this first test, varying the KNO3 concentration, combining with GA3 and the photoperiod. In all experiments the tetrazolium test was carried out on the remaining seeds of the germination test. The percentage of germination, germination speed index (IVG) and percentage of viable seeds were evaluated. It was verified that the seeds present dormancy, being this physiological, and that the treatments with KNO3 in the concentrations of 50 and 100 mM were the most effective in the promotion of the germination and increase of the IVG. However, this effectiveness is directly linked to the concentration of the compounds used.